1997
DOI: 10.1093/ajcn/66.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoenergetic feeding and high-carbohydrate refeeding on muscle tetanic tension, relaxation rate, and fatigue in slow- and fast-twitch muscles in rats

Abstract: Studies using nuclear magnetic resonance have shown that undernutrition affects muscle performance and energetics. It is unclear to what extent underfeeding and refeeding influence the availability of muscle glycogen, net glycogenolysis, skeletal muscle wasting, and recovery. We hypothesized that muscle performance is independent of muscle size and weight, is specific to muscle type, and is unrelated to muscle glycogen concentrations. Slow- and fast-twitch muscles were studied in three groups of adult male Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…Similarly, autopsy samples revealed that glycogen content was reduced in acute and chronic semi starvation [34]. Moreover, Bissonette et al could show that total glycogen values did not seem to affect muscle performance in rats and that net glycogenolysis only correlated with fatigue in the soleus muscle, but not in the extensor digitorum longus muscle [30].…”
Section: Enzyme Kinetics and Substrate Availabi-litymentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, autopsy samples revealed that glycogen content was reduced in acute and chronic semi starvation [34]. Moreover, Bissonette et al could show that total glycogen values did not seem to affect muscle performance in rats and that net glycogenolysis only correlated with fatigue in the soleus muscle, but not in the extensor digitorum longus muscle [30].…”
Section: Enzyme Kinetics and Substrate Availabi-litymentioning
confidence: 97%
“…Also, refeeding improved muscle function in anorexia nervosa patients without simultaneous normalisation of muscle mass [29]. Moreover, Bissonnette et al showed that muscle weight, size and protein did not correlate with muscle function in fast and slow twitch rat muscle during underand subsequent re-feeding [30].…”
Section: Muscle Function Is Restored Faster Than Other Nutritional Inmentioning
confidence: 99%
“…28,29 Through the analysis of biomechanical aspects of muscle, it was found that malnutrition can alter muscular performance in adult rats, even when imposed for short periods, by altering characteristics such as tension, relaxation and fatigue. 30 It remains to be seen whether the elastic properties of tendons and other structures linked to the muscle spindles are also altered by malnutrition, contributing to the lower T-reflexes. Such changes in tendon stiffness have been related to alterations in Treflex amplitudes in the rat 9 and in humans.…”
Section: Figure 3 Mean ± Sd Of the T Max /M Max Ratio During The Matumentioning
confidence: 99%
“…Já a desnutrição, com um menor consenso, parece promover uma redução da atividade de enzimas metabólicas, principalmente, relacionadas ao metabolismo glicolítico (LAYMAN, et al, 1981;RUSSEL et al, 1984a;BISSONNETTE et al, 1997 Diferentemente, com a realização de exercício físico de alta intensidade, por ser um exercício que exige um maior fornecimento de energia pela via glicolítica, ocorre um aumento da atividade dessa enzima no músculo esquelético (ENRIKSSON et al, 1973;GOLLNICK et al, 1974 RUSSEL et al (1984a) e BIOSSONETTE et al (1997, já que o grupo desnutrido sedentário (DS) não apresentou diferença em relação ao eutrófico sedentário (ES). Porém, a não alteração na expressão gênica dessa enzima com a desnutrição não quer dizer, necessariamente, que a atividade dela não possa estar diminuída, como descreveram os últimos autores citados.…”
Section: Discussionunclassified
“…Alguns estudos demonstraram, por exemplo, que a desnutrição promove uma diminuição da expressão de fosfofrutoquinase (PFK) e da succinato desidrogenase (SDH), enzimas da via glicolítica e do ciclo de Krebs, respectivamente (LAYMAN, et al, 1981;RUSSEL et al, 1984a;BISSONNETTE et al, 1997). Além disso, a desnutrição também gera uma diminuição da atividade de enzimas da cadeia respiratória (citocromo c oxidase) no músculo esquelético, além de uma redução da geração de NADH pelo ciclo de Krebs, sugerindo uma diminuição da fosforilação oxidativa e uma alteração do consumo de oxigênio na mitocôndria (FUGE et al, 1968;LAYMAN, et al, 1981;MATECKI et al, 2002).…”
Section: Respostas Adaptativas à Desnutriçãounclassified